Identification of lncRNA and mRNA Expression Profile in Relapsed Graves’ Disease - Yao, Qiuming; Song, Zhenyu; Wang, Bin; Jia, Xi; Song, Ronghua; Zhang, Jinan (Frontiers in Cell and Developmental Biology, 2021)
Background: Graves’ disease (GD) is a common autoimmune disease, and its pathogenesis is unclear. Studies have found that the occurrence of GD is related to the immune disorder caused by the interaction of genetic susceptibility and environmental factors. The CD4+T cell subset is closely related to the immune disorder of GD. LncRNAs are RNA molecules with a length of more than 200 nt and involed in a variety of autoimmune diseases. The study about lncRNAs in recurrent GD is still blank. The purpose of this study is to identify lncRNA and mRNA expression profile in relapsed Graves’ disease. Method: CD4+ T cells from 12 recurrent GD and 8 healthy controls were collected for high-throughput sequencing. The gene-weighted co-expression network analysis (WGCNA) was used to construct the co-expression module relevant to recurrent GD , and the key genes in the module were verified by RT-PCR. Results: Compared with healthy controls, there are 602 up-regulated lncRNAs and 734 down-regulated lncRNAs in CD4+T cells in recurrent GD patients. Through WGCNA, the module most relevant to GD recurrence was constructed, and the key genes in the module were verified by RT-PCR. We found that the expression of RPL8, OAS2, NFAT5, DROSHA, NONHSAT093153.2, NONHSAT118924.2, NONHSAT209004.1 and was significantly decreased in GD group (P<0.001;P<0.001;P<0.01;P<0.05;P<0.001;P<0.05;P<0.01;respectivly). Conclusion: lncRNAs are closely related to the recurrence of GD. For the first time, we constructed the expression profile of lncRNAs and mRNA in CD4+ T cells in recurrent GD patients.